Hollow Co3O4-x nanoparticles decorated N-doped porous carbon prepared by one-step pyrolysis as an efficient ORR electrocatalyst for rechargeable Zn-air batteries - Wang, Yali; Gan, Ruihui; Ai, Zhiquan; Liu, Hao; Wei, Chengbiao; Song, Yan; Dirican, Mahmut; Zhang, Xiangwu; Ma, Chang; Shi, Jingli (Carbon (New York), 2021)
Composites of cobalt oxides and nitrogen-doped porous carbon, as electrocatalysts for oxygen reduction reaction (ORR), offer considerable potential in new-style energy conversion and storage devices. Herein, a straightforward method for production of N-doped porous carbon (Co3O4-‍x@N–C) decorated by hollow Co3O4-x nanoparticles with oxygen vacancies has been studied by one-step pyrolysis of Co-doped quinone-amine polymer in gas mixture of NH3 and Ar. The nanosized CoO/Co3O4 heterostructure can boost the electron transport, while the hollow structure can ensure the structural and chemical stability of the catalyst, and the oxygen vacancy can change the surface electron structure and lower the activation energy barrier for oxygen reduction. Consequently, the as-prepared catalyst Co3O4-x@N–C exhibits excellent ORR catalytic performance (E1/2 = 0.845 V vs. RHE), exceeding that of Pt/C and most recently reported ORR catalysts. The Zn-air batteries assembled with Co3O4-x@N–C present a high open circuit potential (1.524 V), a large peak power density (105.2 mW cm−‍2) and great discharge-charge cycling performance, superior to the Zn-air batteries assembled with Pt/C. The excellent electrocatalytic performances of Co3O4-x@N–C make it an ideal alternative for precious metal catalyst (Pt/C) in rechargeable Zn-air batteries. [Display omitted] •The combination of hollow Co3O4-x nanoparticles with oxygen vacancies and N-doped porous carbon.•The catalyst possesses great ORR catalytic activity, long-cycle durability and methanol resistance.•The assembled Zn-air battery has a peak power density of 105.2 mW cm−2 and a specific capacity of 799.5 mAh g−1.